Effectiveness of Medication and Combination With Surgery Therapy In Reducing Intraocular Pressure On Glaucoma Outpatient at Lavalette Hospital Malang In January 2020 â€“ December 2021 - Aulia Abdul Hamid Abdullah; Priscilla Christina Natan (Syntax Corporation, 2022)
Glaucoma is optic neuropaty group of chronically progressive disorders of the optic nerve that can lead to blidness on the advanced stage. Glaucoma risk factors is elevated intraocular pressure that could damage the optic nerve. Thus, maintaining the intraocular pressure is currently the only modifiable risk factor for the occurrence and progression of glaucoma. This research used retrospective analytical study using secondary data gathered from medical records as total sampling data. The sample was determined by purposive non-probability technique. Mean of intraocular pressure after therapies defined as dependent variable while the independent variable was the type of therapy. Combined therapy (14,40 Â± 3,80 mmHg) had the least post therapy intraocular pressure. Statistical test indicated there is a significant difference in effectiveness on medication, surgery, and combination therapy to glaucoma intraocular pressure reduction. The combined therapies between surgery and medication is more effective in lowering intraocular pressure compared to medication therapy to glaucoma.